Study of Cable Manufacturing Industry with Special Reference to Ravicab Cables Private Limited at Bidadi, Ramanagara District, Karnataka, India - Sathishkumar, H.; Parthasarathy, S. S. (Asian Journal of Electrical Sciences, 2018)
In this paper, cable manufacturing industry (Ravicab cables private limited) at Bidadi is considered for study. This cable industry is using three phase induction motor for its various operations. Mostly, mixing and pushing machine, take up machine, capstan machine and cable drawing machines are in the need of three phase induction motor. In order to control these three phase induction motors, speed controller is essential. Therefore in this study, overall operation of the cable industry, speed controller used in this industry and its defects are discussed. Especially in this industry, Potentiometer (Pot) operated PID (Proportional Derivative Integral) controller based speed controller is used. While using this type of PID based speed controller in the disturbance environment, performance of the speed controller is severely affected.Peformance deterioration of this PID based speed controller is delineated when voltage fluctuation is considered as disturbance environment and also for sudden load changes.